If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 7ln(2x + -1) = 62 Reorder the terms: 6 + 7ln(-1 + 2x) = 62 6 + (-1 * 7ln + 2x * 7ln) = 62 6 + (-7ln + 14lnx) = 62 Solving 6 + -7ln + 14lnx = 62 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -7ln + -6 + 14lnx = 62 + -6 Reorder the terms: 6 + -6 + -7ln + 14lnx = 62 + -6 Combine like terms: 6 + -6 = 0 0 + -7ln + 14lnx = 62 + -6 -7ln + 14lnx = 62 + -6 Combine like terms: 62 + -6 = 56 -7ln + 14lnx = 56 Reorder the terms: -56 + -7ln + 14lnx = 56 + -56 Combine like terms: 56 + -56 = 0 -56 + -7ln + 14lnx = 0 Factor out the Greatest Common Factor (GCF), '7'. 7(-8 + -1ln + 2lnx) = 0 Ignore the factor 7.Subproblem 1
Set the factor '(-8 + -1ln + 2lnx)' equal to zero and attempt to solve: Simplifying -8 + -1ln + 2lnx = 0 Solving -8 + -1ln + 2lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '8' to each side of the equation. -8 + -1ln + 8 + 2lnx = 0 + 8 Reorder the terms: -8 + 8 + -1ln + 2lnx = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1ln + 2lnx = 0 + 8 -1ln + 2lnx = 0 + 8 Combine like terms: 0 + 8 = 8 -1ln + 2lnx = 8 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| (5y+6)(9y+7)=0 | | (3n-2)10=35 | | 3x/2+1/5=3x/5+1/2 | | 6x-1=4x+4 | | 9=3y+5 | | x^2+8x-330=0 | | -8r-7=-24 | | -36=2(x-4) | | 6x+12=30 | | 7x+2=3x+10 | | 20-5n=n+2 | | 4x^2*2x*12=0 | | 15-n=4 | | 4x^2*2x*12= | | 3(8-6n)=24 | | 2x+3=+7 | | 3n+1=n+3 | | 10+2n=0 | | 15-2n=19 | | 5n=200 | | 6n+11=5 | | 5x+29.75=3.25 | | 4n+1=3 | | 35x^2+9x-2=0 | | 10x+5=5x+10+5 | | 2n-3=27 | | 10x+5=5x+10 | | 5n+1=11 | | 7x+6=10x | | 8x+18=2x+174 | | 119-6x=21x+20 | | -98-10x=20-17x |